An assessment of variables affecting transition readiness in pediatric rheumatology patients. Issue 1 (December 2015) - Bingham, Catherine; Scalzi, Lisabeth; Groh, Brandt; Boehmer, Susan; Banks, Sharon
Abstract Background We sought to identify which adolescent patient characteristics might lead to subjective reported independence in accessing medical care when patients transition from pediatric to adult medicine. Methods Pediatric and adult rheumatologists were asked which pediatric patient characteristics they believed would improve transition to adult medical care. Based on these responses, a questionnaire was created and administered to 76 teenage/young adult patients in a pediatric rheumatology clinic. The first set of questions included demographic, disease features, and life skills questions. The second set of questions pertained to self-reported independence in managing medical care. Data was analyzed to see if there were any significant associations between an individual's response to demographic, disease feature, or life skills questions and the independence outcome questions. Results In our study, older age correlated with self-reported independence in almost all questions asked regarding accessing medical care. Other patient characteristics that were associated with increased self-perceived autonomy included having a younger parent, having a family member with a similar disease, longer disease duration, having a comorbid non-rheumatic diagnosis, and having had a summer job. Conclusions The patient characteristics that we found associated with self-reported independence in obtaining medical care should be considered when determining which patients might be more likely to make a successful transition.